Structural Analysis And Electrical Characterisations Of Sr(1-X)Caxtio3 And Sr(1-X)Baxtio3 Ceramics - Ishak, Azizah (2008)
Ceramic samples of a structural formula Sr1-xCaxTiO3 (SCT) and Sr1-xBaxTiO3 (SBT) were prepared from the starting materials CaCO3, BaCO3, SrCO3 and TiO2 through the conventional solid state reaction technique. The XRD measurements reveals that the lattice parameter of SrTiO3 changes after the substitution of Ba2+ and Ca2+ while the specimens, Sr1-xBaxTiO3 and Sr1-xBaxTiO3 showed the typical XRD patterns of perovskite polycrystalline structure without a preferred orientation; no second phase was observed. The crystalline structure and dielectric properties of SCT and SBT ceramics with various compositions of x were investigated. The a- and c-axis lattice constants of SCT and SBT were calculated. It is found that the crystal structures of SBT are cubic phase when x ≤ 0.6 and tetragonal phase when x ≥ 0.7 at room temperature. However, the crystal structures of SCT is orthorhombic when x ≥ 0.1 at room temperature. The dielectric properties such as real permittivity or dielectric constant (ε′), imaginary permittivity or loss factor (ε″) and dielectric loss (tan δ) have been measured on the sintered disks with respect to frequency in the range 0.01 Hz to 1 GHz at room temperature and varying temperatures from 40oC to 200oC. Sample SBT-5 shows the largest value of the real permittivity(ε′ = 4800), low dielectric loss tangent (tan δ = 2.77) and very low ac conductivity (σ = 7.39×10-9 S/cm) at 0.01 Hz. Ceramic sample SCT shows very low dielectric conductivity,σ. The conductivity increases with frequency over the entire temperature range reflecting higher dielectric loss at higher temperature. In the impedance and modulus relaxation spectroscopy, the magnitude of imaginary impedance, Z″ maxima decrease with temperature indicating increasing loss in the resistive property of the sample. This behaviour of impedance pattern arises probably due to the presence of space charge in the material. The activation energy decreases from 0.301 eV to 0.221 eV when the composition of Ca2+ is increased from x = 0.3 to x = 0.9. The electric behavior of sample SBT showed that the activation energy has the value of 0.337 eV and 0.097 eV.